Potential human health risks due to environmental exposure to nano- and microplastics and knowledge gaps: A scoping review - Rahman, Arifur; Sarkar, Atanu; Yadav, Om Prakash; Achari, Gopal; Slobodnik, Jaroslav (The Science of the total environment, 2021)
Microplastics are an emerging global environmental contaminant that are affecting multiple spheres. Despite their ubiquity in all spheres of life and ecology, little is known about the health effects of microplastics exposure to humans. This scoping review explores the existing evidence on the potential human health effects of microplastics and subsequent knowledge gaps. An electronic search of published articles in PubMed, Scopus, EMBASE, Cochrane databases, and Google Scholar was conducted using a combination of subject headings and keywords relating to microplastics and human health effects. The initial search resulted in 17,043 published articles and grey literature documents. After a full review of published articles and their references, 129 publications were identified for further detailed review. These articles indicate that human exposure to microplastics can occur through ingestion, inhalation, and dermal contact due to their presence in food, water, air, and consumer products. Microplastics exposure can cause toxicity through oxidative stress, inflammatory lesions, and increased uptake or translocation. Several studies have demonstrated the potentiality of metabolic disturbances, neurotoxicity, and increased cancer risk in humans. Moreover, microplastics have been found to release their constituent compounds as well as those that are adsorbed onto their surface. Further research is needed to quantify the effects of microplastics on human health and their pathogenesis. [Display omitted] •Microplastics (MPs) are found in every sphere of environment•Scoping review shows a major knowledge gap regarding MPs and human health impacts•Humans are exposed to MPs via ingestion, inhalation, & dermal absorption•MPs might cause oxidative stress, cytotoxicity, and translocation to other tissues•MPs act as vectors for microorganisms & toxic chemicals posing further health risks